Modulatory effects of perindopril on cisplatin-induced nephrotoxicity in mice: Implication of inflammatory cytokines and caspase-3 mediated apoptosis - Aljuhani Naif; Ismail Raed S.; El-Awady Mohammed S.; Hassan Memy H. (Acta Pharmaceutica)
Cisplatin-induced nephrotoxicity limits its anticancer effectiveness, thus this study’s aim was to assess the potential modulatory effect of perindopril on cisplatin-induced nephrotoxicity and to elucidate the possible underlying mechanisms. Renal dysfunction was induced in mice by a single injection of cisplatin (10 mg kg−1, i.p.) and perindopril was administered orally (2 mg kg−1, once daily) for 5 days. Perindopril remarkably ameliorated cisplatin-induced perturbations in renal histology, renal levels of tumor necrosis factor-alpha, interleukin-6 and interleukin-10, apoptosis-regulating protein expressions (Bax and Bcl2), and partially normalized Bax to Bcl2 ratio and active caspase 3 protein expression. Conversely, perindopril had no significant effect on cisplatin-induced elevations in serum creatinine and urea, microalbuminuria, kidney to body weight ratio, lipid peroxidation marker, superoxide dismutase and catalase activities and reduced glutathione content. In conclusion, perindopril may be safely used with cisplatin in mice since it ameliorated cisplatin-induced histopathological changes, inflammation and apoptosis without affecting renal biomarkers or oxidative stress.